Action and object naming in mono- and bilingualchildren with language impairment - Grohmann, Kleanthes K.; Theodorou, Eleni; Kambanaros, Maria (My University, 2010)
Specific Language Impairment (SLI) is a severe limitation in language ability in theabsence of other factors that typically accompany language problems (e.g., hearingimpairment, low non-verbal IQ, neurological damage). SLI is the most common andmost studied type of developmental language disorder, yet research comparing bi- and monolingual development is surprisingly lacking, leaving potential implicationsof bilingualism for children with language disabilities an under-explored area. It isknown that monolingual children with SLI are less accurate at naming pictures of objects than age-matched peers with typical language development (TLD), stronglysuggesting that difficulties with lexical access are related to a breakdown at the levelof the phonological word form, which the present study clearly support.
Keywords: Cypriot Greek; Mono- and bilingual first language acquisition